Problem Based Learning On Literacy Mathematics: Experimental Study in Elementary School - Moch Farhan; Rarasaning Satianingsih; Via Yustitia (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
This research is motivated by the hope of students mastering mathematical literacy skills. Mathematical literacy can facilitate a person in understanding the usefulness of mathematics and applying it in everyday life to make the right decision. But in reality, based on the results of PISA 2018, Indonesia was decreased as a result of The Mathematical Literacy Ability Test. This study aims to determine: (1) The average literacy ability of experimental class students taught through PBL is better than the control class; (2) Class 5 student activities taught using the Problem Based Learning model, (3) Teachers can carry out learning using the Problem Based Learning learning model. This research is quantitative research with observation and documentation methods. The design used is a quasi-experimental design type Post-test only. This research uses an interval scale. The population is grade 5 students of SDN Gayungan II Surabaya. Samples were taken by cluster random sampling technique so that class 5-B (control class) and 5-A (experimental class) were obtained. Data collection techniques used were test methods analyzed with SPSS 22; observation of activities and implementation with descriptive; and documentation. The results showed that: (1) The average literacy ability of the experimental class students taught through PBL was better than the control class; (2) Student activities get very active categories; (3) The implementation of learning using the PBL model gets a Good category. Keywords: Problem Based Learning, Mathematics Literacy Ability.